Rest phase snacking increases energy resorption and weight gain in male mice - Kimberly Begemann; Isabel Heyde; Pia Witt; Julica Inderhees; Brinja Leinweber; Christiane E. Koch; Olaf Jöhren; Rebecca Oelkrug; Arkadiusz Liskiewicz; Timo D. Müller; Henrik Oster (Elsevier, 2023)
Objective: Snacking, i.e., the intake of small amounts of palatable food items, is a common behavior in modern societies, promoting overeating and obesity. Shifting food intake into the daily rest phase disrupts circadian rhythms and is also known to stimulate weight gain. We therefore hypothesized that chronic snacking in the inactive phase may promote body weight gain and that this effect is based on disruption of circadian clocks. Methods: Male mice were fed a daily chocolate snack either during their rest or their active phase and body weight development and metabolic parameters were investigated. Snacking experiments were repeated in constant darkness and in clock-deficient mutant mice to examine the role of external and internal time cues in mediating the metabolic effects of snacking. Results: Chronic snacking in the rest phase increased body weight gain and disrupted metabolic circadian rhythms in energy expenditure, body temperature, and locomotor activity. Additionally, these rest phase snacking mice assimilated more energy during the inactive phase. Body weight remained increased in rest phase snacking wildtype mice in constant darkness as well as in clock-deficient mutant mice under a regular light-dark cycle compared to mice snacking in the active phase. Weight gain effects were abolished in clock-deficient mice in constant darkness. Conclusions: Our data suggest that mistimed snacking increases energy resorption and promotes body weight gain. This effect requires a functional circadian clock at least under constant darkness conditions.